A silicon nitride ion sensitive field effect transistor‐based immunosensor for determination of urinary albumin. Issue 6 (17th November 2021) - Saengdee, Pawasuth; Thanapitak, Surachoke; Ongwattanakul, Songpol; Srisuwan, Awirut; Pankiew, Apirak; Thornyanadacha, Nutthaphat; Chaisriratanakul, Woraphan; Jeamsaksiri, Wutthinan; Promptmas, Chamras
Abstract: The development of an immunosensor‐based biosensor to detect the human serum albumin (HSA) was developed as a low‐cost and label‐free electrical detection through silicon nitride ion‐sensitive field‐effect transistor (Si3 N4 ‐ISFET). This sensor was functionalized using 3‐Aminopropyltriethoxysilane (APTES). The silanized Si3 N4 ‐ISFET surface was covalently linked with antibody against HSA (Anti‐HSA) via glutaraldehyde (GA) to function as an HSA immunosensor for detection of HSA. The interaction between HSA and Anti‐HSA on this device is monitored by changing of the gate potential at a constant drain current of 50 μA. The relationship between HSA concentration and the gate potential change of HSA immunosensor is linear up to 500 μg/ml with a detection limit of 5 μg/ml. This HSA immunosensor offers a good precision in both intra‐ and inter‐assay with a relative standard deviation of 6.61%, 7.48%, 10.69%, and 9.67%, 13.16%, 15.52% for 100, 200, and 400 μg/ml. The average percentage of recovery assay for the concentration of 32.1, 102.1, and 202.1 μg/ml is 96.55%. This sensor also provides its satisfactory selectivity when testing with Bence Jones protein solution. In addition, the results that was done by this HSA immunosensor is similar to the conventional method using immunoturbidimetric detection with a linear regression of 0.99; n = 40 with a paired sample t ‐test of <0.01. Thus, this HSA immunosensor could be applied to urinary microalbumin detection because of its simplicity and satisfactory correlation value.